Pelatihan Pembuatan Komik Edukatif Pencegahan Kekerasan di SD Inpres Lere dengan Bantuan ChatGPT - Ady Irawan; Edy Suparjan; Roni Irawan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
This training program is designed to instill anti-violent values through visual storytelling in the form of educational comics created by teachers themselves, adapted to the cultural context and environment of students. This initiative stems from the need for teachers to have engaging, relevant, and effective learning media to prevent violence in elementary schools. The Service Learning (SL) method integrates academic learning with social services, emphasizing direct experience through activities such as designing, discussing, and practicing the skills taught. The training begins with an introductory session on the forms and dynamics of violence in elementary schools, followed by an introduction to comics as a medium for communicative learning. The next stage is comic-making training, in which participants design stories grounded in anti-violence values, covering the following themes: norms in everyday life, anti-bullying, peaceful conflict resolution, the courage to report, deliberations on forming a violence-prevention team, and the character